EFFECT OF ECONOMIC HARDSHIP ON ENTREPRENEURIAL STRESS: A STUDY ENTREPRENEURS IN SOUTH-EAST NIGERIA - Nwanonyere, Chika (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
Entrepreneurs have contributed significantly to the development and growth of many nations and have assumed a ubiquitous part of the business ecosystem. It contributes positively to employment generations and has been broadly considered the primary driver of socio-economic development and wealth creation. However, there are indications that the increasing economic downturns have been unfavorable to entrepreneurs. Thus, the purpose of the present paper was to examine the economic hardship as a factor that could explain the variation in entrepreneurial stress. A convenience sample of two hundred and thirteen entrepreneurs pooled from different business hubs in the Enugu and Anambra state of Nigeria participated in the study. The simple regression analysis conducted to test the hypothesis revealed that economic hardship statistically significantly predicted entrepreneurial stress F (1,211), 32.61, P<.000. Thus, the result affirmed the assumption that economic hardship would significantly predict entrepreneurial stress. In addition, the R2 showed that economic hardship explained about 46.3% of the variance in entrepreneurial stress. The paper concluded that economic hardship is an essential factor in entrepreneurial stress